Crystallization and preliminary neutron diffraction experiment of human farnesyl pyrophosphate synthase complexed with risedronate - Yokoyama, Takeshi (International Union of Crystallography, 2014)
Nitrogen-containing bisphosphonates (N-BPs), such as risedronate and zoledronate, are currently used as a clinical drug for bone-resorption diseases and are potent inhibitors of farnesyl pyrophosphate synthase (FPPS). X-ray crystallographic analyses of FPPS with N-BPs have revealed that N-BPs bind to FPPS with three magnesium ions and several water molecules. To understand the structural characteristics of N-BPs bound to FPPS, including H atoms and hydration by water, neutron diffraction studies were initiated using BIODIFF at the Heinz Maier-Leibnitz Zentrum (MLZ). FPPS–risedronate complex crystals of approximate dimensions 2.8 × 2.5 × 1.5 mm (∼3.5 mm(3)) were obtained by repeated macro-seeding. Monochromatic neutron diffraction data were collected to 2.4 Å resolution with 98.4% overall completeness. Here, the first successful neutron data collection from FPPS in complex with N-BPs is reported.